HUBUNGAN KECERDASAN EMOSIONAL DENGAN MOTIVASI BELAJAR SISWA (Kasus SMP Swasta HKBP Pematangsiantar) - Bangun Munte; Darman Samosir (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2019)
ABSTRACT The purpose of this study was to look at the relationship of emotional intelligence with student motivation in Pematangsiantar HKBP Private Middle School. The number of samples was 57 people. This research uses descriptive method, while the data analysis conducted using Pearson product moment correlation with data collection tools is a questionnaire for Variable X (emotional intelligence) and Variable Y (student learning motivation). To determine the relationship of emotional intelligence with student learning motivation, Pearson Product Moment Correlation Statistical Test was used. From the test results obtained by testing the correlation (r) 0.48 with a determination test of 23.04% and to find out whether or not the correlation coefficient is significant at the real level (α) = 0.05, a